Serum Vitamin D Level is Inversely Associated With Anti-Cyclic Citrullinated Peptide Antibody Level and Disease Activity in Rheumatoid Arthritis Patients - Yanan WANG; Fengwei ZHANG; Shanshan WANG; Xuechai SHANG; Siyuna LUO; Hongjuan ZHOU; Huaping SHI; Long CAI (Archives of Rheumatology, 2016)
Objectives: This study aims to assess the relationship between serum vitamin D and anti-cyclic citrullinated peptide (anti-CCP) antibody levels, as well as disease activity in patients with newly diagnosed rheumatoid arthritis (RA). Patients and methods: These measurements were conducted between January 2014 and June 2014. Serum 25-hydroxy vitamin D (25-OH-D), anti- CCP antibody, and erythrocyte sedimentation rates were measured in a cohort of 154 patients (66 males, 88 females; mean age 53.5±12.4; range 29 to 79 years) with early RA. A control group of 60 healthy participants (25 males, 35 females; mean age 51.4±10.3; range 25 to 75 years) was only evaluated for serum 25-OH-D levels. Disease activity was measured by calculating the 28-Joint Disease Activity Score. Blood samples were drawn from cubital veins. After centrifugation, serum was collected and stored under minus 20 degrees. Results: Vitamin D deficiency was more prevalent in RA group compared with control group (48.70% vs. 30.00%, p<0.05). Serum 25-OH-D levels were lower in RA group (19.46±8.20 ng/mL) than control group (23.18±6.71 ng/mL) (p<0.05). In the RA group, serum 25-OH-D levels were negatively correlated to anti-CCP antibody levels (rs= –0.360, p<0.001), erythrocyte sedimentation rate (rs= –0.270, p<0.001), age of patients (rs= –0.602, p<0.001), and disease activity (rs= –0.249, p<0.05), respectively. Serum 25-OH-D level did not vary according to sex in the RA group. In control group, females had lower serum 25-OH-D level (p=0.001, rs=0.404). In addition, serum 25-OH-D level was also negatively associated with age in control group (p<0.001, rs= –0.578). There were no differences between RA group and control group in terms of age and sex ratio. Conclusion: Serum 25-OH-D level was negatively correlated to anti-CCP antibody level and disease activity, which implied the therapeutic role of serum 25-OH-D in RA.